Ice-sheet scale distribution and morphometry of triangular-shaped hummocks (murtoos): a subglacial landform produced during rapid retreat of the Scandinavian Ice Sheet - Antti E. K. Ojala; Gustaf Peterson; Joni Mäkinen; Mark D. Johnson; Kari Kajuutti; Jukka-Pekka Palmu; Elina Ahokangas; Christian Öhrling (Cambridge University Press, 2025)
High-resolution digital elevation models of Finland and Sweden based on LiDAR (Light Detection and Ranging) reveal subglacial landforms in great detail. We describe the ice-sheet scale distribution and morphometric characteristics of a glacial landform that is distinctive in morphology and occurs commonly in the central parts of the former Scandinavian Ice Sheet, especially up-ice of the Younger Dryas end moraine zone. We refer to these triangular or V-shaped landforms as murtoos (singular, ‘murtoo’). Murtoos are typically 30–200 m in length and 30–200 m in width with a relief of commonly <5 m. Murtoos have straight and steep edges, a triangular tip oriented parallel to ice-flow direction, and an asymmetric longitudinal profile with a shorter, but steeper down-ice slope. The spatial distribution of murtoos and their geomorphic relation to other landforms indicate that they formed subglacially during times of climate warming and rapid retreat of the Scandinavian Ice Sheet when large amounts of meltwater were delivered to the bed. Murtoos are formed under warm-based ice and may be associated with a non-channelized subglacial hydraulic system that evacuated large discharges of subglacial water